Abdominal Subcutaneous and Visceral Adipose Tissue and Insulin Resistance in the Framingham Heart Study - Preis, Sarah R. (2010)
Insulin resistance is associated with central obesity and an increased risk of cardiovascular disease. Our objective is to examine the association between abdominal subcutaneous (SAT) and visceral adipose tissue (VAT) and insulin resistance, to determine which fat depot is a stronger correlate of insulin resistance, and to assess whether there was an interaction between SAT, VAT, and age, sex, or BMI. Participants without diabetes from the Framingham Heart Study (FHS), who underwent multidetector computed tomography to assess SAT and VAT (n = 3,093; 48% women; mean age 50.4 years; mean BMI 27.6 kg/m(2)), were evaluated. Insulin resistance was measured using the homeostasis model and defined as HOMA(IR) ≥75th percentile. Logistic regression models, adjusted for age, sex, smoking, alcohol, menopausal status, and hormone replacement therapy use, were used to assess the association between fat measures and insulin resistance. The odds ratio (OR) for insulin resistance per standard deviation increase in SAT was 2.5 (95% confidence interval (CI): 2.2–2.7; P < 0.0001), whereas the OR for insulin resistance per standard deviation increase in VAT was 3.5 (95% CI: 3.1–3.9; P < 0.0001). Overall, VAT was a stronger correlate of insulin resistance than SAT (P < 0.0001 for SAT vs. VAT comparison). After adjustment for BMI, the OR of insulin resistance for VAT was 2.2 (95% CI: 1.9–2.5; P < 0.0001). We observed an interaction between VAT and BMI for insulin (P interaction = 0.0004), proinsulin (P interaction = 0.003), and HOMA(IR) (P interaction = 0.003), where VAT had a stronger association in obese individuals. In conclusion, SAT and VAT are both correlates of insulin resistance; however, VAT is a stronger correlate of insulin resistance than SAT.